The making of capital cities between the Arab world and subsaharian Africa: Nouakchott (Mauritania) and Karthoum (Sudan), a comparative approach. - (:unkn) unknown (My University, 2006)
Nouakchott and Khartoum are capital cities standing in-between the Arab world and subsaharian Africa. Such transitional position gives rise to stakes and conflicts: these two cities are set in an environment stressed by antagonistic identities. Throughout a comparative approach, this study tries to explain how these spatial entities are built and analyses the interactions which exist between political logics (the capital as a power instrument) and social dynamics (the city, to which the inhabitants first adapted before appropriating it). In Mauritania and Sudan, the states' leaders have used these political territories to establish their arabizing tendancies. These capitals have become supports for the arab identity at the expense of an important part of the african population, thus increasing the gap between the different social groups. Facing up to this ideoligical urban making, the inhabitants build their own city – remote from the ideal arabic capital – and create a new urbanity.
Keywords: African Research